Earthquake Prediction using SVM based Time Predictable Technique - Shanti, M.A (International Journal of Computer Sciences and Engineering, 2025)
As with so many natural phenomena, earthquakes are the product of what scientists call "complex systems," or systems which are more than the sum of their parts. Not just speaking proverbially, but in truest ever sense, precise prediction of earthquakes has long been a question of Life & Death for the scared inhabitants of earthquake-prone areas and so is for the forecasters and scientists ranging from Nostradamus to Dr. Vladimir Kellis-Borok since last a few centuries. Though the experts still don’t know many of the details of the physical processes involved and how to predict these events, several prediction and chaos theories have been put forth with varying degrees of successes. In spite of the inherent complexities involved in such a complex system, the research is still on and on. The time- predictable model of earthquake prediction is based on the theory that earthquakes in fault zones are caused by the constant build-up and release of strain in the Earth's crust. This model has become a standard tool for hazard prediction in many earthquake-prone regions and, therefore, it is not surprising that the scientists in the United States and other Pacific Rim countries, such as Japan and New Zealand, routinely use this technique for long-range hazard assessments when adequate data are available